Impacts and perspectives of prenyltransferases of the DMATS superfamily for use in biotechnology - Fan, Aili; Winkelblech, Julia; Li, Shu-Ming (Applied microbiology and biotechnology, 2015)
Prenylated compounds are ubiquitously found in nature and demonstrate interesting biological and pharmacological activities. Prenyltransferases catalyze the attachment of prenyl moieties from different prenyl donors to various acceptors and contribute significantly to the structural and biological diversity of natural products. In the last decade, significant progress has been achieved for the prenyltransferases of the dimethylallyltryptophan synthase (DMATS) superfamily. More than 40 members of these soluble enzymes are identified in microorganisms and characterized biochemically. These enzymes were also successfully used for production of a large number of prenylated derivatives. N1-, C4-, C5-, C6-, and C7-prenylated tryptophan and N1-, C2-, C3-, C4-, and C7-prenylated tryptophan-containing peptides were obtained by using DMATS enzymes as biocatalysts. Tyrosine and xanthone prenyltransferases were used for production of prenylated derivatives of their analogs. More interestingly, the members of the DMATS superfamily demonstrated intriguing substrate and catalytic promiscuity and also used structurally quite different compounds as prenyl acceptors. Prenylated hydroxynaphthalenes, flavonoids, indolocarbazoles, and acylphloroglucinols, which are typical bacterial or plant metabolites, were produced by using several fungal DMATS enzymes. Furthermore, the potential usage of these enzymes was further expanded by using natural or unnatural DMAPP analogs as well as by coexpression with other genes like NRPS and by development of whole cell biocatalyst.